2010
DOI: 10.1007/s10815-010-9420-9
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility in China: laboratory finding for AZF microdeletions and chromosomal abnormalities in infertile men from Northeastern China

Abstract: Purposes To investigate the frequencies of AZF microdeletions and chromosomal abnormalities in infertile men from Northeastern China. Moreover, to compare the prevalence of these abnormalities with other countries and regions in the world. Methods 305 infertile men were enrolled. A complete semen analysis and reproductive hormones were measured according to standard methods. Multiplex polymerase chain reaction (PCR) amplification using nine specific sequencetagged sites (STS) were used to detect AZF microdelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
9
29
0
3
Order By: Relevance
“…It is clear that men with large deletions of Yq are infertile but large deletions of the Yq-chromosome are rarely found. Several investigations have shown that 10-15 % of infertile men with azoospermia or severe oligozoospermia have small deletions of the Yq-chromosome, which are not detectable in a karyotype test [8]. A study performed on 3073 infertile men found that Yq microdeletions were detected in 5.5 % of patients who suffered from oligozoospermia and in 8.3 % of those suffering from non-obstructive azoospermia [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that men with large deletions of Yq are infertile but large deletions of the Yq-chromosome are rarely found. Several investigations have shown that 10-15 % of infertile men with azoospermia or severe oligozoospermia have small deletions of the Yq-chromosome, which are not detectable in a karyotype test [8]. A study performed on 3073 infertile men found that Yq microdeletions were detected in 5.5 % of patients who suffered from oligozoospermia and in 8.3 % of those suffering from non-obstructive azoospermia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Microdeletions of azoospermia factor (AZF) loci on the long arm of the Y chromosome are a major cause of male infertility in populations throughout the world (Mitra et al, 2006;Li et al, 2008;Wang et al, 2010). As early as 1976, Tiepolo and Zuffardi followed by other authors postulated that genes and gene families located on locus 11 of the Y chromosome long arm (Yq11) were associated with male germ cell development (Ambasudhan et al, 2003;Wang et al, 2010;Behulova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Microdeletions of azoospermia factor (AZF) loci on the long arm of the Y chromosome are a major cause of male infertility in populations throughout the world (Mitra et al, 2006;Li et al, 2008;Wang et al, 2010). As early as 1976, Tiepolo and Zuffardi followed by other authors postulated that genes and gene families located on locus 11 of the Y chromosome long arm (Yq11) were associated with male germ cell development (Ambasudhan et al, 2003;Wang et al, 2010;Behulova et al, 2011). It was later found that microdeletions of four subregions of the AZF region (AZFa, AZFb, AZFc, and AZFd) led to various types of spermatogenesis impairments, from teratozoospermia to infertility, with different population distributions depending on their Y haplogroup profile (Li et al, 2008;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations